PENGARUH KINERJA KEUANGAN PERBANKAN TERHADAP HARGA SAHAM (Students' Journal of Accounting and Banking, 2014)
In this study population taking banking companies listed on the Stock Exchange in the period 2008 - 2012, with sampling using purposive sampling method was obtained as much as 116 samples. Based on the research that has been done it can be seen Adequancy Capital Ratio (CAR) and a significant positive ef fect on stock prices. Therefore , the first hipothesis (Hl): CAR positive effect on the stock price, is accepted. Return on Assets risked ( RORA ) and is a significant positive effect on stock prices. Thus the second hypothesis (H2 ): RORA positive effect on stock prices, declined. Operating Expense to Operating Income (OEOI) and a significant positive effect on stock prices. Thus the third hypothesis (H3): OEOI positive effect on stock prices, acceptable. Earning per Share (EPS) and a signi ficant positive effect on stock prices. Therefore, the fourth hypothesis (H4 ): Earnings per Share (EPS) positive ef fect on stock p rices, acceptable. Loans to Deposits Ratio (LDR) Positive effect on stock prices. Therefore, the fifth hypothesis (H5): LDR positive effect on stock prices " acceptable.Keywords: Adequancy Capital Ratio, Return on Assets risked, Operating expense to Operating Income, Earnings Per Share, Loan to Deposit Ratio and Stock Price